2007
DOI: 10.1002/lt.21206
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation for children in Brazil weighing less than 10 kilograms

Abstract: Infants with end-stage liver disease represent a treatment challenge. Living donor liver transplantation (LDLT) is the only option for timely liver transplantation in many areas of the world, adding to the technical difficulties of the procedure. Factors that affect morbidity and mortality can now be determined, which opens a new era for improvement. We have accumulated an 11-year experience with LDLT for children weighing Ͻ10 kg. From October 1995 to October 2006, a total of 222 LDLT in patients Ͻ18 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 30 publications
4
48
0
2
Order By: Relevance
“…In consistent with previous 2 studies of children who had the Kasai operation for correction of biliary atresia, and those children in the pretransplant scenario exhibited malnutrition and hyperbilirubinemia. 26,27 We observed that female sex was associated with greater morbidity, similar to a previous study from Kyoto that reported that female sex and high GRWR were independent risk factors for hepatic artery thrombosis after LDLT. 28 To our knowledge, few studies have reported outcomes of ICU-bound pediatric patients after LDLT.…”
Section: Discussionsupporting
confidence: 87%
“…In consistent with previous 2 studies of children who had the Kasai operation for correction of biliary atresia, and those children in the pretransplant scenario exhibited malnutrition and hyperbilirubinemia. 26,27 We observed that female sex was associated with greater morbidity, similar to a previous study from Kyoto that reported that female sex and high GRWR were independent risk factors for hepatic artery thrombosis after LDLT. 28 To our knowledge, few studies have reported outcomes of ICU-bound pediatric patients after LDLT.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the fact that children under one year of age represent one out of four pediatric LTx recipients (2), infants with end-stage liver disease remain a challenging and understudied group. While it has been well documented that infants historically have had the highest rates of wait-list mortality amongst all pediatric candidates (3–6), only a limited number of studies exist which investigate the outcomes of these youngest LTx recipients (719). To date these prior series have struggled with small sample sizes, reported wide variation in outcomes, and have been unable to clearly identify risk factors of survival for infants undergoing LTx.…”
Section: Introductionmentioning
confidence: 99%
“…Jurim (1995) [79] USA R/C LT/RLT 0-10 Not described HAT 29% (LT) vs. 0% (RLT) Kamel (2006) [80] Ireland R/C KT 0-18 None GT 5% Kanmaz (2014) [13] Turkey R/C LT 0-18 ASA HAT 3.9%, PVT 6.8% Karatzas (1997) [81] USA R/C LT All Not described HAT 11.4% Khan (2014) [82] Saudi Arabia R/C KT 0- [86] Italy R/C LT, < 6 kg 0-1 Not described HAT 0%, PVT 6% [12] Switzerland R/C LT 0-18 UFH, ASA, FFP HAT 1.8%, PVT 0.9% Millis (1996) [19] USA R/C LDLT/RLT 0-3 Not described ePVT 4-33%; dPVT 4-51% Miyagi (2014) [88] Japan R/C LDLT All Protease inhibitor Not reported Nagra (2004) [48] UK R/C KT 0-17 UFH vs. No prophylaxis GT 8% vs. 11% Neto (2007) [89] Brazil P/C LDLT < 10 kg 0-18 Not described HAT 3.1%, PVT 5.4% Neto (2012) [10] Brazil P/C LDLT 0-18 Not described HAT 4.3%, ePVT 2.6%, dPVT 5.8% Neto (2014) [90] Brazil P/C LDLT 0-18 UFH/VKA in high risk, dipyridamole PVT 7%…”
Section: Thromboprophylaxismentioning
confidence: 99%